Recanalization Rates after Acute Deep Vein Thrombosis: A Single-center Experience Using a Newly Proposed Vein Diameter Variation Index - Brandao, Gustavo M. S. [UNESP]; Sobreira, Marcone Lima [UNESP]; Malgor, Rafael D.; Rollo, Hamilton Almeida [UNESP] (Elsevier B.V., 2014)
Background: Duplex ultrasound scanning (DUS) is the method of choice for diagnosis of deep vein thrombosis (DVT). However, only a few studies have performed prospective serial DUS after an acute episode of DVT to assess its evolution. This study aimed to report our experience using DUS combined with a thrombosis score (TS) and a newly proposed vein diameter variation index (VDVI) to evaluate the rate of resolution of DVT by assessing and quantifying the early stages of vein recanalization in proximal vein segments within 6 months after an episode of acute lower extremity DVT.Methods: Twelve patients with first episode of acute lower extremity DVT confirmed by DUS as occurring in <= 10 days after the onset of venous thrombosis symptoms were followed up prospectively for 6 months. TS and VDVI were calculated at 1, 3, and 6 months to assess vein recanalization. Intra-thrombus arteriovenous fistula formation was also investigated and related to the recanalization process.Results: Seven (58%) women were included, with a total cohort median age of 53.5 +/- 19 years. The left lower extremity was affected in 7 (58%) patients. DVT was diagnosed in 55 proximal vein segments. All patients had proximal DVT, with involvement of the external iliac, femoral, and popliteal veins. After 6 months, there was a significant decrease in TS and increase in VDVI (P < 0.001) in all proximal vein segments assessed, indicating thrombus regression. The more distal the DVT was, the faster was the VDVI increase, with most popliteal veins being recanalized at 3 months (P < 0.001). Intra-thrombus arteriovenous fistula was identified in 50% of patients at 1 month while on anticoagulation.Conclusions: The combined use of two different DUS-based assessment tools, TS and the proposed VDVI, provided an effective method to prospectively assess vein recanalization rates after an episode of acute lower extremity DVT in this series of patients and may allow a correct evaluation of DVT and its resolution or progression.